The Effect Of Return On Investment And Earning Per Share On Stock Price As A Moderating Variable. - Haslindah, Haslindah; Sudirman, Sitti Rahma; Saleh, Wahyuni; Herman, Bahtiar (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
This study aims to determine the effect of return on investment and earnings per share on company stock prices with perceived stock risk as a moderating variable. The population in this study are mining sector companies listed on the Indonesia Stock Exchange 2018-2020. Sampling was done by purposive sampling technique. Data analysis techniques were performed using descriptive statistical analysis and PLS (Partial Least Square). Based on the analysis that has been done, the results of Return On Investment (ROI) have a positive and significant effect on stock prices. Earning Per Share (EPS) has a positive and significant effect on stock prices. Return On Investment (ROI) has a positive and significant effect on stock prices moderated by perceived stock risk. Earning Per Share (EPS) has a positive and significant effect on stock prices moderated by perceived stock risk